Wearable and flexible electrochemical sensors for sweat analysis: a review - Gao, Fupeng; Liu, Chunxiu; Zhang, Lichao; Liu, Tiezhu; Wang, Zheng; Song, Zixuan; Cai, Haoyuan; Fang, Zhen; Chen, Jiamin; Wang, Junbo; Han, Mengdi; Wang, Jun; et al. (Microsystems & nanoengineering, 2023)
Flexible wearable sweat sensors allow continuous, real-time, noninvasive detection of sweat analytes, provide insight into human physiology at the molecular level, and have received significant attention for their promising applications in personalized health monitoring. Electrochemical sensors are the best choice for wearable sweat sensors due to their high performance, low cost, miniaturization, and wide applicability. Recent developments in soft microfluidics, multiplexed biosensing, energy harvesting devices, and materials have advanced the compatibility of wearable electrochemical sweat-sensing platforms. In this review, we summarize the potential of sweat for medical detection and methods for sweat stimulation and collection. This paper provides an overview of the components of wearable sweat sensors and recent developments in materials and power supply technologies and highlights some typical sensing platforms for different types of analytes. Finally, the paper ends with a discussion of the challenges and a view of the prospective development of this exciting field.